MEANINGS OF SEXUALITY FOR YOUNG AND ITS CONSEQUENCES IN PREVENTIVE BEHAVIOR (Fiep Bulletin - online, 2012)
Despite the development of methods of prevention and the young people's access to information on sexuality, it is still great the number of teenage pregnancies and their exposure to STDs. The research seeks to correlate the social representation of young women's sexuality with the adopted sexual behavior. Interviews with 29 women from 15 to 24 years of age were submitted to content analysis and to the Alceste software. The results revealed representations of sexuality focused on affection, which conflicts with sexual freedom and with the notion that young women have of prevention. Thus, the divergence between the reality experienced and the reality that is merely implied stops adolescents from adopting preventive actions regarding sexual intercourse. These findings direct all levels of attention on sexuality to the importance of understanding what young people think before offering them sexual guidance, whose information purpose would be to promote the reshaping of representations which undermine prevention.
Keywords: Pregnancy in adolescence; sexual orientation; Sexual Health.